Arab Women in Algeria - Auclert, Hubertine (De Gruyter, 2014)
The book presents the first English edition of Hubertine Auclert's Arab Women in Algeria which offers a unique picture of Algerian society in late 19th century. Hubertine Auclert (1848-1914) was one of the foremost militants for women's political rights in France from the mid-1870s. She lived in Algeria from 1888 to 1892, where she investigated the customs and traditions that defined the condition of women. She witnessed both the exploitation of women and that of the colonized people; in doing so, she drew a picture of colonial Algerian society. While women were mistreated by men (sale of prepubescent girls into marriage, forced marriage, repudiation permitted only to men, polygamy), Arab men were mistreated by the colonial administration and excluded from the government of Algeria. She denounced the contradictions and hypocrisy of French justice, which often enforced, for their own interest, the "anomalies" of Muslim law in contradiction with French law. The last chapter of the book comprises of several striking anecdotes that illustrate the author's theoretical views.